A Novel Haptic device with High-force Display Capability and Wide workspace - Lee, Giuk; Hur, Sung-moon; Oh, Yonghwan (2016 IEEE INTERNATIONAL CONFERENCE ON ROBOTICS AND AUTOMATION (ICRA), 2016)
This paper presents a novel haptic device, named VirtuaPower, having abilities of 6 degrees of freedom (DOF) position measurement with a high-force display capability and wide workspace. The VirtuaPower is designed as a parallel mechanism with double in-parallel supporting chains. The mechanical design is presented with constraints and space Jacobians. The workspace and force display capability are computed via kinematic analysis. The VirtuaPower has a wide workspace up to 1 m(3) (semicylinder, diameter 1.8 m x height 1.0 m). Moreover, the force display capability is enhanced compared to any existing haptic device, i.e., approximately 100 N of linear force and 10 Nm of torque. The force display ability is validated by an experiment with a 6 DOF force/torque sensor. Finally, a simple virtual reality environment is experientially realized with the VirtuaPower to show its utility as a haptic device.